Microstructure dependence of fatigue crack propagation behavior in wrought magnesium alloy (Fracture and Structural Integrity, 2015)
This paper deals with the fatigue crack propagation behavior of rolled AZ31B magnesium alloy (grain size: approximately 40 ?m). Fatigue crack propagation tests were performed on single edge notched tension specimens at a stress ratio of R = 0.1 and a frequency of 10 Hz at room temperature. Loading axes were parallel to the rolling direction; fatigue cracks propagated parallel to the transverse direction (L-T specimen), parallel to the short transverse direction (L-S specimen). Loading axis was perpendicular to the rolling direction; fatigue cracks propagated parallel to the transverse direction (S-T specimen). The crack growth rate (da/dN) of the L-S specimen was several times lower than that of the L-T specimen in the examined stress intensity factor range (?K). Fracture surfaces of the L-T and L-S specimens showed many steps parallel and perpendicular, respectively, to the macroscopic crack growth direction. The da/dN of the S-T specimen was higher than that of the L-T and L-S specimens in the examined ?K. The fracture surface was covered by quasi-cleavage facets independent of macroscopic crack growth direction, and the fracture surface roughness at low ?K was larger than that at high ?K.
Keywords: Fatigue crack; Texture; Magnesium